2022
DOI: 10.3389/fnins.2022.957012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between interaural delay in binaural gap detection and sensitivity to temporal fine structure in young adults with or without musical training experience

Abstract: Humans can detect the presence of a break in interaural correlation (BIC, also called binaural gap) even if a large interaural time delay (ITD) is introduced, which is important for detecting, recognizing, and localizing sounds in everyday environments. To investigate the relationship between interaural delay in binaural gap detection and the sensitivity of temporal fine structure (TFS), 40 young college students with normal hearing took the BIC delay threshold test, the TFS1 test (the test of monaural TFS sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Preschool children with CIs have been reported to perform similarly to their hearing peers in CBCL measurements after one year of implant use [17 ]. It has also been reported that deaf children successfully cope with social and school-life demands, regardless of their speech and language success after CI [17][18][19][20]. Our study shows a significant difference between the CAP variable's 0-5 year and > 6-year groups (p=0.017).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Preschool children with CIs have been reported to perform similarly to their hearing peers in CBCL measurements after one year of implant use [17 ]. It has also been reported that deaf children successfully cope with social and school-life demands, regardless of their speech and language success after CI [17][18][19][20]. Our study shows a significant difference between the CAP variable's 0-5 year and > 6-year groups (p=0.017).…”
Section: Discussionsupporting
confidence: 66%
“…It was observed that they actively participate in school and sports activities, as in the normal-hearing student group [18]. Compared with the normative language acquisition process, it shows that these children develop expressive and receptive oral language skills and have linguistic skills patterns under their chronological age.…”
Section: Discussionmentioning
confidence: 95%